Characteristics Comparison of Neon, Argon, and Krypton Ion Emissions from Gas Field Ionization Sources with a Single-Atom Tip. (30th January 2019) - Shichi, Hiroyasu; Matsubara, Shinichi; Hashizume, Tomihiro
Abstract: A scanning ion beam instrument equipped with a gas field ionization source (GFIS) has been commercialized, but only helium and neon are currently available as GFISs. In this study, the characteristics of neon, argon, and krypton ion emissions from a single-atom tip are compared, specifically for faster fabrication by milling of a silicon sample. Although the boiling point of argon is about 87 K, our experiments on characterizing argon ion emission can be carried out at temperatures of about 50 K at an argon gas pressure lower than 0.1 Pa. Argon exhibits ion current characteristics, as a function of tip voltage, between those of neon and krypton. The value obtained by multiplying the ion emission current by the sputtering yield is suitable for a figure of merit (FOM) for faster fabrication. The FOM for argon is the highest among the three ion species. This value must be extensively evaluated from the viewpoint of practical nano-fabrication application. The instabilities of neon, argon, and krypton ion currents (3 σ ) become as low as 8% in 1 h, which is sufficient for fabrication applications. We conclude that an argon or krypton GFIS ion beam instrument will be a useful tool for nano-fabrication.